A bovine myeloid antimicrobial peptide (BMAP‐28) kills methicillin‐resistant Staphylococcus aureus but promotes adherence of the bacteria. (25th August 2013) - Takagi, Shiaki; Bai, Lanlan; Ozeki, Tomomitsu; Miyagi, Hikaru; Kuroda, Kengo; Hayashi, Shunji; Yoneyama, Hiroshi; Ando, Tasuke; Isogai, Emiko
Abstract The cathelicidin family is one of the several families of antimicrobial peptides (AMPs). A bovine myeloid antimicrobial peptide (BMAP‐28) belongs to this family. Recently, the emergence of drug‐resistant bacteria such as methicillin‐resistant Staphylococcus aureus (MRSA) has become a big problem. AMPs are expected to be leading compounds of new antibiotics against drug‐resistant bacteria. In this study, we focused on the activity of BMAP‐28 against bacterial cell surfaces. First, we observed morphological change of MRSA caused by BMAP‐28 using a scanning probe microscope. We also studied activities of BMAP‐28 against adherence of S. aureus to fibronectin, collagen type I, collagen type IV. We confirmed whether BMAP‐28 can bind to lipoteichoic acid (LTA) of S. aureus. BMAP‐28 was indicated as damaging the cell surface of MRSA. In a particular range of concentrations, BMAP‐28 promoted adherence of S. aureus against fibronectin and collagens. It was revealed that BMAP‐28 and LTA of S. aureus bound with each other. Our study showed the potential of BMAP‐28 which can damage MRSA and interact with LTA of S. aureus but promote its adherence in some concentrations. This study provides new points of which to take notice when we use AMPs as medicines.